The role of electron spin in molecular photochemical and photophysical processes: theory and experiment - Faraji, Shirin; Kleinschmidt, Martin; Engels, Bernd; Dreuw, Andreas (Physical chemistry, chemical physics, 2025)
This themed issue of Physical Chemistry Chemical Physics is dedicated to Professor Christel Maria Marian (Christel) on the occasion of her 70th birthday, celebrating her immense contributions to the field of Theoretical and Computational Chemistry over several decades. Her remarkable work has not only enriched our understanding of molecular photochemical and photophysical processes but has also fostered a vibrant community within chemistry in Germany and Europe.
Zuerst veröffentlicht: 30. Oktober 2025
Gesehen am 03.12.2025